Biological observations on the common guitarfish Rhinobatos rhinobatos from Iskenderun Bay (Turkey, Eastern Mediterranean) - Cek, Sehriban; Basusta, Nuri; Demirhan, Sefa Ayhan; Karalar, Murat (Brill, 2009)
Histological examination of the gonads showed that spermatogenesis occurs in every male R. rhinobatos collected in autumn and winter months of the year. The testis was composed of lobes having numerous spermatocysts in a dorsoventral zonated arrangement. Present results suggest that since R. rhinobatos have a cystic mode of spermatogenesis it can be used as a model for biomedical and toxicological studies. Eight stages of maturation for females and seven stages of maturation for males were identified. Moreover, vitellogenic oocytes were consistently found in every female collected during the summer months. In vitellogenic oocytes, yolk is present as pleomorphic droplets and very often; small yolk droplets have a crystalline configuration. These data suggest that both sexes are reproductively active at different times of the year. Both, the right ovary/testis and the left ovary/testis were functional. Ripe oocytes in the ovaries were usually symmetrically distributed. The population consisted of aplacental viviparous individuals with lecithotrophic embryo development. Although, sex ratios of R. rhinobatos were not significantly different from the expected 1:1 ratio (p>0.05), slightly female biased sex ration were recorded. (C) Koninklijke Brill NV, Leiden, 2009
Keywords: Rhinobatos rhinobatos; gametogenesis; reproductive cycle; sex ratio; Turkey; Eastern Mediterranean